Coronary Vasospasm after Giving Adenosine for Supraventricular Tachycardia - Naredi, Mohit; Bharani, Anil (International Journal of Cardiovascular Practice, 2019)
Palpitations due to supra-ventricular tachycardia are a common mode of presentation to the emergency department. A 12 lead electrocardiography usually leads to immediate diagnosis and prompt management of this condition. Adenosine injection is the treatment of choice for rapid termination of supra-ventricular tachycardia which is widely used. It is generally considered safe and serious side effects are rare. We presented a rare case of a post-menopausal female admitted with supra-ventricular tachycardia and after injection of Adenosine, chest pain with a transient elevation of ST segment occurred. The ST segment changes reverted back to normal after a few minutes spontaneously without any therapy. This phenomenon could be explained due to coronary vasospasm produced by Adenosine. A review of literature revealed anecdotal cases of adenosine induced possible coronary vasospasm.